BA 260 - Small Business Management - Linn Benton Virtual College (2018)
This course focuses on the entrepreneurial phases associated with start-up and management of small business. This course will teach future entrepreneurs and managers to recognize opportunities and to use effective entrepreneurial and small business management practices.